Association between food insecurity and depression among older adults from low‐ and middle‐income countries. Issue 4 (9th March 2021) - Smith, Lee; Il Shin, Jae; McDermott, Daragh; Jacob, Louis; Barnett, Yvonne; López‐Sánchez, Guillermo F.; Veronese, Nicola; Yang, Lin; Soysal, Pinar; Oh, Hans; Grabovac, Igor; Koyanagi, Ai
Abstract: Background: To examine the association between self‐reported food insecurity and depression in 34, 129 individuals aged ≥50 years from six low‐ and middle‐income countries (LMICs) (China, Ghana, India, Mexico, Russia, and South Africa). Methods: Cross‐sectional, community‐based, nationally representative data from the WHO Study on global AGEing and adult health (SAGE) were analyzed. Self‐reported past 12‐month food insecurity was assessed with two questions on frequency of eating less and hunger due to lack of food. Questions based on the World Mental Health Survey version of the Composite International Diagnostic Interview were used for the endorsement of past 12‐month DSM‐IV depression. Multivariable logistic regression analysis and meta‐analysis were conducted to assess associations. Results: In total, 34, 129 individuals aged ≥50 years [mean ( SD ) age, 62.4 (16.0) years; 52.1% females] were included in the analysis. Overall, the prevalence of moderate and severe food insecurity was 6.7% and 5.1%, respectively, while the prevalence of depression was 6.0%. Meta‐analyses based on countrywise estimates showed that overall, moderate food insecurity (vs. no food insecurity) is associated with a nonsignificant 1.69 (95% confidence interval [CI] = 0.82–3.48) times higher odds for depression, while severe food insecurity is significantly associated with 2.43 (95% CI = 1.65–3.57) times higher odds for depression. Conclusions: In this large representative sample of older adults from six LMICs, those with severe food insecurity were over two times more likely to suffer from depression (compared with no food insecurity). Utilizing lay health counselors and psychological interventions may be effective mechanisms to reduce depression among food‐insecure populations. Interventions to address food insecurity (e.g., supplemental nutrition programs) may reduce depression at the population level but future longitudinal studies are warranted.